Kanggoroo Mother Care as a Method to Increase the Weight of Premature Babies with Fenton Chart Monitoring: A Health Promotion Program - Syamsidah Lubis; Hafaz Zakky Abdillah; Arvitamuriany Triyanthi Lubis; Fera Wahyuni (Sumatera Medical Journal, 2025)
Background: Premature birth is defined as the birth of a baby before 37 weeks gestation. Kangaroo Mother Care (KMC) is a care technique, particularly beneficial for premature infants, that emphasizes skin-to-skin contact between the mother and her baby. Research shows that KMC significantly reduce the number of neonatal deaths, preventing hypothermia, reducing the occurrence of infections, increasing baby growth and development, increasing breastfeeding and bonding between mother and baby. Objective: To emphasize the importance of Kangaroo Mother Care for premature infants and address the barriers that may affect its implementation. Methods: A review of current literature and research findings related to Kangaroo Mother Care was conducted, focusing on health benefits and common challenges to its application in different settings. Results: KMC significantly reduce neonatal deaths, prevent hypothermia, reduce infections, and support baby growth and development. It also increases breastfeeding and bonding between mother and baby. However, some beliefs may restrict physical contact with newborns or dictate other types of care that do not involve close, continuous contact. Conclusion: Kangaroo Mother Care is an effective method for improving outcomes in premature infants. Therefore, it is important to educate healthcare workers and mothers the importance of Kangaroo Mother Care to promote its adoption and overcome cultural barriers.